Legal Analysis of the Authority of Notaries to Issue Covernotes to Banks - Miradz Pratama, Andyka (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
A covernote is a certificate issued by a notary in banking practice as a statement that the deed creation and credit guarantee binding process is ongoing. Although commonly used by banks as a basis for credit disbursement, the notary's authority to issue a covernote is not explicitly regulated in the Notary Law. This condition raises legal issues related to the notary's position, binding power, and liability in the event of default or loss to the bank. This study aims to analyze the notary's authority to issue a covernote and its legal implications in banking practice. The research method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that a covernote is not an authentic deed and does not have perfect evidentiary power, so the notary does not have attributive authority to issue it. However, a covernote still creates legal liability for the notary based on the principles of prudence and professionalism.